2013
DOI: 10.1371/journal.pone.0065083
|View full text |Cite
|
Sign up to set email alerts
|

Gamete Therapeutics: Recombinant Protein Adsorption by Sperm for Increasing Fertility via Artificial Insemination

Abstract: A decrease in fertility can have a negative economic impact, both locally and over a broader geographical scope, and this is especially the case with regard to the cattle industry. Therefore, much interest exists in evaluating proteins that might be able to increase the fertility of sperm. Heparin binding proteins (HBPs), specifically the fertility associated antigen (FAA) and the Type-2 tissue inhibitor of metalloproteinase (TIMP-2), act to favor the capacitation and acrosome reaction and perhaps even modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
(27 reference statements)
0
8
0
2
Order By: Relevance
“…Heparin binding proteins such as TIMP2 are acquired by the sperm during ejaculation, and expression have been identified in the bovine accessory sex glands (McCauley et al, 2001; Moura et al, 2006). Recombinant TIMP2 along with other heparin binding proteins, have been added to bovine semen before cryopreservation and AI, under tropical conditions, with a resulting positive effect on pregnancy rate (Alvarez‐Gallardo et al, 2013). NPC2 and TIMP2 have both previously been identified in SP from electroejaculated B. indicus bulls (Rego et al, 2014) and a previous study by our group identified NPC2, clusterin (CLU), and metalloproteinase inhibitor 2 to correlate negatively with the PNS (Boe‐Hansen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Heparin binding proteins such as TIMP2 are acquired by the sperm during ejaculation, and expression have been identified in the bovine accessory sex glands (McCauley et al, 2001; Moura et al, 2006). Recombinant TIMP2 along with other heparin binding proteins, have been added to bovine semen before cryopreservation and AI, under tropical conditions, with a resulting positive effect on pregnancy rate (Alvarez‐Gallardo et al, 2013). NPC2 and TIMP2 have both previously been identified in SP from electroejaculated B. indicus bulls (Rego et al, 2014) and a previous study by our group identified NPC2, clusterin (CLU), and metalloproteinase inhibitor 2 to correlate negatively with the PNS (Boe‐Hansen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, elephant sperm were affected by a dilution effect and restoration of SP proportion with stallion SP improved the motility of chilled highly diluted sperm. Further identification of this supportive component may benefit the development of an appropriate extender or may allow treatment with direct addition to sperm used for AI in elephant, as has been carried out in bovine (Alvarez‐Gallardo et al., ) and in more sophisticated techniques in ram (Zalazar, Ledesma, Hozbor, & Cesari, ).…”
Section: Discussionmentioning
confidence: 99%
“…kimia heparin menyerupai glycosaminoglycans (GAGs) yang disekresikan dalam saluran reproduksi sapi betina (Alvarez-Gallardo et al 2013). Heparin dan GAGs pada saluran reproduksi sapi betina akan berikatan dengan protein pada permukaan sperma sapi jantan.…”
Section: Molekulunclassified